1995
DOI: 10.1515/znb-1995-0716
|View full text |Cite
|
Sign up to set email alerts
|

A Fluorine-Containing Cryptand for the Complexation of Anions and the Utility of 19F NMR Spectroscopy for the Determination of Host-Guest Association

Abstract: The first fluorine-containing cryptand F3-TREN 4 for the complexation of anions was prepared in the 3 + 2-condensation reaction of 2-fluoro-1,3-phthalaldehyde 3 with tris(2-aminoethyl) amine and subsequent reduction with NaBH4. Upon incorporation of anionic guests 4 ·6HClO4 experiences shifts of its 19F NMR resonances and thus demonstrates the advantages of studying host-guest association by 19F NMR spectroscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 9 publications
1
27
0
Order By: Relevance
“…Melting points were determined with a Meltemp melting point apparatus in sealed capillaries. Starting materials were available commercially or prepared according to literature procedures: 1,3-dimethyl-2-fluorobenzene, 1,3-bis(bromomethyl)-2-fluorobenzene, HO 5 , diaza-18-crown-6, aza-12-crown-4, aza-15-crown-5 and aza-18-crown-6, triflate salts, and picrate salts . Picrate extraction experiments were carried out according to a procedure by Cram et al and were performed under the same conditions used to reproduce the literature values for dicyclohexano-18-crown-6 …”
Section: Methodsmentioning
confidence: 99%
“…Melting points were determined with a Meltemp melting point apparatus in sealed capillaries. Starting materials were available commercially or prepared according to literature procedures: 1,3-dimethyl-2-fluorobenzene, 1,3-bis(bromomethyl)-2-fluorobenzene, HO 5 , diaza-18-crown-6, aza-12-crown-4, aza-15-crown-5 and aza-18-crown-6, triflate salts, and picrate salts . Picrate extraction experiments were carried out according to a procedure by Cram et al and were performed under the same conditions used to reproduce the literature values for dicyclohexano-18-crown-6 …”
Section: Methodsmentioning
confidence: 99%
“…A well-documented recipe for preparing azacyclophanes calls for macrocyclization by imine formation followed by reduction. , Strong but size-dependent complexation of oxoanions is observed with monocyclic as well as with bicyclic members such as 38a 201 of this class. Efficient binding of nucleotides reaching log K assn of 4−5 202 is found in dilute acid and probably is of the inclusion type, as suggested by a number of crystal structures. , …”
Section: Positively Charged Anion Hostsmentioning
confidence: 99%
“…London and Gabel [146] reported fluorobenzene boronic acid, which interacted with specific sugars. Plenio and Diodone [147] reported fluorine containing cryptands, which interact with perchlorate. These investigators have also reported a series of fluorocyclophanes and fluoro crown ethers to explore specific cation binding (e.g., K + , Li + , Na + , Ba 2+ , Sr 2+ , Ca 2+, and associated chemical shifts [136,148].…”
Section: Other Biological Relevant Ligandsmentioning
confidence: 99%